لانغستون هيوز: مفهوم الزنجي الجديد وعقدة الانتماء - حاتم سكينة (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This article aims to show the difficulties African writers faced in American society due to the fact that the literary canon was mistakenly represented and confined to white American writers. The criterion problem triggers subsequent problems manifested in the internal and external conflict of African writers in improving their literary presence in American society. Langston Hughes tries to fathom the problem of integration with its two folds: physical and cultural. Hughes’s poems raise the quintessential question of accepting and embracing the black identity by black writers themselves so that they can be accepted by others in American society. Hughes’s emphasis on his racial focus in his poems constitutes an incentive for other black writers to accept their black identity and produce it in their writings. يهدف هذا البحث إلى إظهار المصاعب التي واجهت الكتاب الأفريقيين في المجتمع الأمريكي بالاستناد إلى حقيقة أن الميزان الأدبي قد تم تقديمه وحصره بطريقة خاطئة بين الكتاب البيض الأمريكيين. وقد أدى التقديم الخاطئ للميزان الأدبي إلى ظهور مشكلات أخرى تمثلت في الصراع الداخلي والخارجي للكتاب الإفريقيين في تحسين حضورهم الأدبي في المجتمع الأمريكي. وقد حاول لانغستون هيوز سبر أغوار مشكلة الانتماء بشقيها الثقافي والجسدي, فطرحت قصائده السؤال الجوهري الذي يدور حول قبول الكتاب السود أنفسهم؛ الشخصية السوداء؛ ليقبلهم الآخرون في المجتمع الأمريكي. وشكل تأكيد هيوز على الهوية العرقية في قصائده حافزاً للكتاب السود الآخرين لدفعهم إلى قبول هويتهم وإبرازها في كتاباتهم.